Like a dark rabbi : modern poetry & the Jewish literary imagination - Finkelstein, Norman, 1954- (Cincinnati : Hebrew Union College Press, 2019)
"Wallace Stevens' "dark rabbi," from his poem "Le Monocle de Mon Oncle," provides a title for this collection of essays on the "lordly study" of modern Jewish poetry in English. Including chapters on such poets as Charles Reznikoff, Allen Grossman, Chana Bloch, and Michael Heller, this volume explores the tensions between religious and secular worldviews in recent Jewish poetry, the often conflicted linguistic and cultural matrix from which this poetry arises, and the complicated ways in which Jewish tradition shapes the sensibilities of not only Jewish, but also non-Jewish, poets. Finkelstein, described as "one of American poetry's indispensible makers" (Lawrence Joseph), whose previous critical work has been called "the exemplary study of the religious aspect of the works of contemporary American poets" (Peter O'Leary), considers large literary and cultural trends while never losing sight of the particular formal powers of individual poems. In Like a Dark Rabbi, he offers a passionate argument for the importance of Jewish-American poetry to modern Jewish culture, and to American poetry more broadly, as it engages with the contradictions of contemporary life."--
Preface -- Introduction: two Shapiros: thoughts on poetry and secular Jewish culture -- Ghosts of Yiddish; or, postvernacularity in Jewish American poetry -- Charles Reznikoff: modernism, diaspora, and the problem of Jewish identity -- Allen Grossman and the poetry of holiness -- Michael Heller: between the sacred and the profane -- Chana Bloch: surfaces and depths -- "The darker wisdom of the Jews": Henry Weinfield's dialectical irony -- Rachel Tzvia back: between Israel and the diaspora -- Dark rabbis and secret Jews -- Afterword: "diasporas of imperfection."
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: American poetry -- Jewish authors -- History and criticism; American poetry -- 20th century -- History and criticism; American poetry -- 21st century -- History and criticism; Jews -- United States -- Identity; Jews in literature; Judaism and literature -- United States; Judaism in literature; Jewish religious poetry, American -- History and criticism; Judaism and secularism; Poésie américaine -- 20e siècle -- Histoire et critique; Juifs -- États-Unis -- Identité.; Juifs dans la littérature.; Judaïsme et littérature -- États-Unis.; Judaïsme dans la littérature.; Poésie religieuse juive américaine -- Histoire et critique; LITERARY CRITICISM -- Jewish; American poetry; American poetry -- Jewish authors; Jewish religious poetry, American; Jews -- Identity; Jews in literature; Judaism and literature; Judaism and secularism; Judaism in literature; United States; 1900-2099; Criticism, interpretation, etc